1999
DOI: 10.1101/gad.13.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bicoid-related homeodomain factor Pitx1 in specifying hindlimb morphogenesis and pituitary development

Abstract: Pitx1 is a Bicoid-related homeodomain factor that exhibits preferential expression in the hindlimb, as well as expression in the developing anterior pituitary gland and first branchial arch. Here, we report that Pitx1 gene-deleted mice exhibit striking abnormalities in morphogenesis and growth of the hindlimb, resulting in a limb that exhibits structural changes in tibia and fibula as well as patterning alterations in patella and proximal tarsus, to more closely resemble the corresponding forelimb structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
329
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(343 citation statements)
references
References 54 publications
8
329
1
5
Order By: Relevance
“…This and the finding that Pitx1 is expressed only in the hindlimb suggested a role in the determination of hindlimb morphology and identity. [11][12][13][14] The hypothesis was supported by studies performed in chick and mouse showing that misexpression of Pitx1 in forelimbs results in the adoption of hindlimb characteristics. 14,15 In fish, pelvic loss in different natural populations of stickleback fish has occurred through regulatory mutations deleting a tissue-specific enhancer of Pitx1 and demonstrates an evolutionary change in vertebrates via this genomic region.…”
Section: Discussionmentioning
confidence: 93%
“…This and the finding that Pitx1 is expressed only in the hindlimb suggested a role in the determination of hindlimb morphology and identity. [11][12][13][14] The hypothesis was supported by studies performed in chick and mouse showing that misexpression of Pitx1 in forelimbs results in the adoption of hindlimb characteristics. 14,15 In fish, pelvic loss in different natural populations of stickleback fish has occurred through regulatory mutations deleting a tissue-specific enhancer of Pitx1 and demonstrates an evolutionary change in vertebrates via this genomic region.…”
Section: Discussionmentioning
confidence: 93%
“…Primary sequence analysis revealed multiple putative cis-elements for the homeobox transcription factor Pitx-1 (25), which is highly expressed in the PT and PD cells of ventral origin, trans-activates many pituitary-specific genes, and is involved in gonadotroph development (13)(14)(15). Transient transfection assays clearly demonstrated that Pitx-1 strongly stimulates MT 1 promoter activity, and suggest that the proximal doublet of Pitx-1 sites is critical to this effect.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the strongest expression of Pitx-1 occurs in the PT and in PD cells of ventral origin (13), and therefore overlaps with the expression profile of pituitary melatonin receptors. Furthermore, mice bearing a genetic lesion of the Pitx-1 gene exhibit a selective decrease in ventral PD thyrotroph and gonadotroph cells, and also in ''PT-specific'' thyrotrophs (15). Because these cell types are associated with melatonin receptor expression in rodents (16,17), the possibility arises that Pitx-1 may be an important factor supporting melatonin receptor expression in the adenohypophysis.…”
mentioning
confidence: 99%
“…Misexpression of Pitx1 in the developing chick wing can, at least partially, transform both muscle and skeletal elements of the forelimb and give them a more hindlimb-like character (Logan and Tabin, 1999;Takeuchi et al, 1999). In Pitx1 null mice, the hindlimb does form, but features of hindlimb identity are lost and the limb has a more forelimb-like character (Lanctot et al, 1999;Szeto et al, 1999). For example, the diameters of the tibia and the fibula in the Pitx1 mutant limb are similar to those of the homologous elements in the forelimb, the radius and the ulna, respectively.…”
Section: Pitx1 and Pitx2 Cooperate In Hindlimb Developmentmentioning
confidence: 99%
“…Mouse No forelimb (Agarwal et al, 2003; Hindlimb initiated but no limb outgrowth Hindlimb forms but hindlimb characteristics lost (Lanctot Rallis et al, 2003) (Naiche andPapaioannou, 2003) et al, 1999;Szeto et al, 1999;Marcil et al, 2003) Chick No wing (Rallis et al, 2003;Takeuchi et al, No hindlimb (Takeuchi et al, 2003;N/D 2003;Ng et al, 2002) Ng et al, 2002 Zebrafish No pectoral fin (Ng et al, 2002;Ahn et al, N/D N/D 2002;Garrity et al, 2002) N/D = not determined.…”
Section: Tbx5mentioning
confidence: 99%